Increasing Adolescents' Knowledge in Indonesia of HIV and STD in Leading-Up Three Zero HIV/AIDS 2030 - Indiastari, Dewi; Setyowati, Lita; Sutanto, Heri; Budiarti, Niniek; Rosandi, Millanitalia; Dwitarahma, Marshandyar (Clinical and Research Journal in Internal Medicine, 2024)
During the transition period of puberty, adolescents experience physical, psychological, and ways of thinking, which social and environmental changes will have a significant impact on adolescents. Improper self-control becomes a threat that can damage the morale and future of adolescents, including choosing the wrong environment resulting in drug abuse, unwanted pregnancies, abortions, sexually transmitted infections, HIV, and AIDS. This community service activity aims to increase the knowledge and importance of youth awareness in Malang about HIV and STIs. This activity is an online lecture-based activity (webinar) and live event assisting teenagers in Malang area. It is held for seven weeks by providing education about what HIV is, why it must be avoided—the dangers of sexually transmitted infections online followed by a discussion session. The activity was attended by 763 participants aged 10-20 years and 114 guardians of students and laypeople. The results obtained during the activity showed an increase in the post-test scores compared to the values before getting the webinar. A long-term evaluation still needs to be carried out to assess the absorption rate of the material that has been carried out on the quality of life of webinar participants. The conclusion obtained from this activity is that the knowledge of webinar participants, especially teenagers, about HIV/AIDS has increased, and knowledge is a fundamental thing that must be instilled in adolescents as early as possible to prevent HIV transmission in adolescents.